2012
DOI: 10.1111/j.1600-0722.2011.00919.x
|View full text |Cite
|
Sign up to set email alerts
|

Survivin gene promoter polymorphism ‐31G/C as a risk factor for keratocystic odontogenic tumor development

Abstract: Several single nucleotide polymorphisms in survivin gene promoters, notably -31G/C, have been shown to modulate the expression and activity of the survivin protein. Consequently, the -31G/C polymorphism has been identified as a risk factor for the development of several types of tumors. The aim of this study was to investigate a possible association between the -31G/C polymorphism and the risk for keratocystic odontogenic tumor (KCOT) development. DNA from 52 biopsy specimens of KCOTs and from 82 buccal swabs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
1
13
0
2
Order By: Relevance
“…that the C allele has a protective role. Similar results have already been obtained for another type of benign tumours in the Serbian population, the keratocystic odontogenic tumours (38), as well as in one type of malignancy -Wilm's tumours (39).…”
Section: Discussionsupporting
confidence: 74%
“…that the C allele has a protective role. Similar results have already been obtained for another type of benign tumours in the Serbian population, the keratocystic odontogenic tumours (38), as well as in one type of malignancy -Wilm's tumours (39).…”
Section: Discussionsupporting
confidence: 74%
“…As for survivin rs9904341, the ultimate analysis included four gastric cancer studies [28], [29], [30], [31], three hepatocellular cancer studies [20], [32], [33], three colorectal cancer studies [34], [35], [36], two esophageal [18], [37] and two bladder cancer studies [19], [21], as well as twelve studies of other tumors [16], [17], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47]. Overall, 8 studies used Caucasians, 17 used Asians, one used mixed populations.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to our results, carrying G allele for survivin -31 C/G has reported that increased cancer risk in renal cell carcinoma (Qin et al, 2012), stomach cancer (Borges et al, 2011) and lung cancer (Jang et al, 2008) studies. Additionally, GG genotype for survivin -31 C/G polymorphism has been shown a risk factor in keratocystic odontogenic tumor development (Andric et al, 2012). Aynaci et al (2013) has reported that individuals carrying survivin 31 GC genotype had a significantly decreased risk of having non-small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%